Angiogenesis Regulated by Electroacupuncture Combined with Rehabilitation Training in Cerebral Ischemia Involved in PI3K/Akt Signaling Pathway - Wenchao YAO; Mengxing LI; Qing LIU; Mingyue TONG; Peng HE; Wei TANG (康复学报)
Objective:Based on the phosphatidylinositol 3-kinase (PI3K) /protein kinase B(Akt) signal pathway, to explore the regulatory mechanism of electroacupuncture combined with rehabilitation training on angiogenesis after cerebral ischemia.Methods:A total of 81 SPF male SD rats were randomly divided into three groups: sham operation group, model group and electroacupuncture combined with rehabilitation training group (combined acupuncture group). The right middle cerebral artery occlusion (MCAO) model was established by using Zea longa external carotid artery thread occlusion method. In the sham operation group, only the carotid artery was separated without ligation or insertion. The sham operation group and the model group were not given any treatment. The combined acupuncture group was given electroacupuncture at acupoints of Baihui, Fengfu, Xinshu and Neiguan, and treadmill training 4 hours after operation, once a day for 14 days. The ultrastructure of neurons in ischemic area was observed by transmission electron microscope. Microvessel density (MVD) of ischemic side was detected by immunohistochemistry. The relative expression levels of vascular endothelial growth factor (VEGF), brain-derived neurotrophic factor (BDNF), PI3K and Akt were detected by Western blot and RT-PCR respectively.Results:(1) The neurons in the ischemic area of the model group were irregular in morphology, vacuolation, reduction of glycosomes and autophagic vesicles in the cytoplasm, swelling of mitochondria and pyknosis of nucleus; Compared with the model group, on day 3, 7 and 14 of treatment, the neuron cell membrane of the combined acupuncture group showed a tendency to repair, and the structure of organelles and the degree of vacuolation were significantly improved.(2) On day 3, 7 and 14 of treatment, the MVD count of cerebral ischemia area was statistically significant in different groups (FIntergroup=141.762, P< 0.001), the MVD count of the combined acupuncture group was higher than that of the other two groups, the difference was statistically significant respectively (P< 0.01); On day 3, 7 and 14 of treatment, there was significant difference in the change trend of different time points respectively (FTime=81.920, P< 0.001), the combined acupuncture group increased significantly on the 14th day of treatment, and the differences were statistically significant (P< 0.01); MVD count had group×time obvious interaction (FInteraction=44.960, P< 0.001). (3) The variance analysis of repeated measurements of VEGF, BDNF, PI3K, Akt proteins in the brain tissue of the ischemic area showed that the variables were statistically significant among different groups respectively (FIntergroup=398.772, 903.082, 2 312.264, and 1 581.880, P< 0.001). The expression of protein in the combined acupuncture group was higher than that of the other two groups, and the difference was statistically significant respectively (P< 0.01); the trend of each variable at different time points was significantly different respectively (FTime=100.462, 53.714, 106.552, 75.381, P< 0.001), the expression of VEGF and Akt protein in the model group increased on the 7th day, and the difference was statistically significant compared with 3 d and 14 d respectively (P< 0.05); the expression of BDNF and PI3K increased on the 7th day in the model group, compared with that on the 3rd day, the difference was statistically significant (P< 0.01); the expression of VEGF, BDNF, PI3K, Akt protein increased significantly on the 14th day of the combined acupuncture group, and the difference was statistically significant compared with 3 d and 7 d respectively (P< 0.05); The expression group×time all had a significant interaction (P< 0.001). (4) The analysis of variance of repeated measurements of VEGF, BDNF, PI3K, Akt mRNA in rat brain tissues in ischemic area showed that the variables were statistically significant in different groups respectively (FIntergroup=445.845, 427.743, 918.388, 543.814, P< 0.001), the combined acupuncture group expression was higher than the other two groups, the difference was statistically significant respectively (P< 0.01); the change trend of each variable at different time points was significantly different (FTime=100.343, 13.984, 9.162, 32.931, P< 0.001), the expression of BDNF and PI3K mRNA in the model group increased on the 7th day, and the difference was statistically significant respectively (P< 0.05, P< 0.01); the expression of VEGF mRNA in the model group increased on the 7th day, compared with that on the 14th day, the difference was statistically significant (P< 0.01); the expression of VEGF, BDNF, PI3K, Akt mRNA increased significantly on the 7th day in the combined acupuncture group, and the difference was statistically significant compared with 3 d and 14 d respectively (P< 0.05, P< 0.01); the mRNA expression group×time had significant interaction (P< 0.001).Conclusion:Under the influence of intervention effect, time effect and the interaction of the two, the combination of electroacupuncture and rehabilitation training can play a protective role in cerebral ischemia, which may be related to the control of the expression of VEGF and BDNF and the downstream transduction pathway PI3K/Akt, which mediates the angiogenesis after cerebral ischemia.